Pengaruh Live Streaming dan Online Review terhadap Purchase Intention melalui Trust pada Generasi Z di E-Commerce - Prianda Saputra; Ryna Parlyna; Inkreswari Retno Hardini (INDO PUBLISHING, 2026)
This research is motivated by the increasing use of live streaming and online reviews as digital stimuli in shaping consumer trust and purchase intentions, especially Generation Z as digital natives. This study uses a quantitative approach with a survey method of Generation Z aged 18-28 years who live in East Jakarta and are active Shopee users. The sampling technique used purposive sampling, with data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that live streaming and online reviews have a positive and significant effect on trust and purchase intention. In addition, trust is proven to significantly mediate the influence of live streaming and online reviews on purchase intention. This finding confirms the important role of trust in driving Generation Z's purchase intention on the Shopee e-commerce platform.